Profiling reading in print and digital mediums. (October 2018) - Singer Trakhman, Lauren M.; Alexander, Patricia A.; Silverman, Alexis B.
Abstract: Real-time processing behaviors and processing time for 57 undergraduates reading information texts in print and digitally were used to identify distinct performance profiles. Students underlined the printed text as they read and followed along with their cursor when reading digitally. Immediately after reading, students answered three comprehension questions for each text about the main idea, key points, and other information and judged their performance on the comprehension test. Four profiles were identified using deeper and more surface-level processing behaviors and reading time for both mediums (i.e. Regulators, Plodders, Gliders, and Samplers) and comprehension and calibration (i.e., self-assessment accuracy) data were analyzed by medium and profile. An overall medium effect for comprehension, along with various profile differences were identified. No overall calibration difference by medium was found, although various effects by profile were identified. Implications of outcomes for future research on reading in print and digitally are forwarded. Highlights: Four processing profiles were identified using deeper and more surface-level processing behaviors and reading time for both mediums. An overall medium effect for comprehension, along with various profile differences were identified. No overall calibration difference by medium was found, although effects by profile types were identified. Implications of outcomes for future research on reading in print and digitally are forwarded.